Changing Trends in Melanoma Incidence and Decreasing Melanoma Mortality in Hungary Between 2011 and 2019: A Nationwide Epidemiological Study - Liszkay, Gabriella; Kiss, Zoltan; Gyulai, Roland; Oláh, Judit; Holló, Péter; Emri, Gabriella; Csejtei, András; Kenessey, István; Benedek, Angela; Polányi, Zoltán; Nagy-Erdei, Zsófia; Daniel, Andrea; et al. (Frontiers in Oncology, 2021)
Background: The incidence of malignant melanoma has continually increased during the past few decades, however, certain reports suggest a recent change in trends. The aim of our study was to examine the epidemiology of melanoma in Hungary. Methods: This nationwide, retrospective, longitudinal study included melanoma patients diagnosed between 1 January 2009 and 31 December 2019 using the databases of the National Health Insurance Fund (NHIF) and Central Statistical Office (CSO) of Hungary. Age-standardized incidence and cause-specific mortality rates were calculated. Results: We identified 2,426 and 2,414 new melanoma cases in 2011 and in 2019. Age-standardized incidence rates were higher in males and varied between 28.28 and 34.57/100,000 person-years (PYs), and between 22.63 and 26.72/100,000 PYs in females. We found 16.14% and 18.82% increases in male and female incidence rates from 2011 to 2015 (p=0.067 and p<0.001, respectively), and 12.77% and 11.35% decreases from 2015 to 2019 (p=0.062 and p=0.004, respectively). The change of incidence trends (2011–2015 vs. 2015–2019) was significant in females (p=0.002) and in the total melanoma population (p=0.011), but not in the male population (p=0.063). A 16.55% (95% CI: -27.07 to -4.59; p=0.013) decrease in mortality rates was found in the overall melanoma population. Conclusions: We observed a significant trend change in melanoma incidence in the female and total melanoma population, and a significant decrease in mortality in the total melanoma population. These changes may be attributed to intensive melanoma awareness campaigns as well as to the increase in screening and access to modern therapies.